Faktor-Faktor yang Mempengaruhi Kepatuhan Minum Obat Pada Pasien Skizofrenia: Factors Affecting Medication Adherence in Patients with Schizophrenia - Randy Refnandes; Zakiah Almaya (NERS Jurnal Keperawatan, 2021)
Medication non-adherence is a major problem in the treatment of people with schizophrenia, if left untreated, can cause various impacts including relapse and decreased quality of. The purpose of this study was to determine the factors that influence medication adherence in people with schizophrenia The method in this study with schizophrenia literature review by identifying research articles published in 2015-2020 using 3 databases namely Pubmed, Science Direct, and Google Scholar. The research articles were selected using PRISMA. used10 reviewed articles were obtained and extracted in tabular form. The results of the article analysis showed that the factors that influence medication adherence in people with schizophrenia include patient factors age, gender, income, education insight, and attitude. Treatment factors were the amount of drug, type of drug, side effects of the drug, severity of symptoms, and duration of treatment. And environmental factor were family support, social support, residence, and nurse-client relationships. people with schizophrenia, especially nurses, have to provide health education for patients and families about the importance of medication adherence and for future researchers, it is advise that further researchers to investigate the factors that influence medication adherence in schizophrenic patients and interventions to improve medication adherence in schizophrenic patients.